Histone chaperones in nucleosome assembly and human disease - Burgess, Rebecca J (2013)
Nucleosome assembly following DNA replication, DNA repair and gene transcription is critical for the maintenance of genome stability and epigenetic information. Nucleosomes are assembled via replication-coupled or replication-independent pathways with the aid of histone chaperone proteins. How these different nucleosome assembly pathways are regulated remains relatively unclear. Recent studies have provided insight into the mechanisms and the roles of histone chaperones regulating nucleosome assembly. Alterations or mutations in factors involved in nucleosome assembly have also been implicated in cancer and other human diseases. This review highlights the recent progress and outlines future challenges in the field.